Harmonic Effects of Power System Loads: An Experimental Study - Kocatepe, Celal; Yumurtacı, Recep; Arıkan, Oktay; Baysal, Mustafa; Kekezoğlu, Bedri; Bozkurt, Altuğ; Kumru, C. Fadıl (IntechOpen, 2013)
None